Anisotropic magnetoresistance and planar Hall effect in an antiferromagnetic insulator-topological insulator heterostructure - Yuxin Liu; Yongqing Li; Jing Teng (Physical Review Research)
The coupling between magnetism and topological states at a topological insulator (TI)-magnetic insulator interface can induce exchange gap opening and spin texture change, resulting in many emergent transport phenomena, including anisotropic magnetoresistance (AMR) and planar Hall effect (PHE). While AMR/PHE have been reported in several ferromagnetic insulator-TI heterostructures so far, such effects in antiferromagnetic insulator-TI heterostructure remain elusive. Here, we observe unique features of AMR and PHE in an antiferromagnetic insulator-TI heterostructure MnSe/(Bi,Sb)_{2}Te_{3}. Specifically, at low magnetic fields (H), the in-plane AMR exhibits dips under H applied parallel to the current (H//I) but peaks under the perpendicular geometry (H⊥I), opposite to the zero AMR features in ferromagnetic insulator-TI heterostructures. The low-field PHE is most striking at H//I, but gradually suppressed when H deviates from parallel direction. At high magnetic fields, both AMR and PHE show prominent π-period oscillation. Gate-tuning and temperature-dependence measurements demonstrate that the observed AMR/PHE originate from the interplay between the topological surface state of TI with the spin canting and magnetic phase transition of MnSe. These results not only differentiate the AMR/PHE in TI-based magnetic heterostructure from the pristine TI, but also offer a feasible way to distinguish spin Hall effect and AMR in TI-based heterostructures.